2014
DOI: 10.1111/cen.12536
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and hypertensive cardiomyopathy in patients with a relapse‐free history of phaeochromocytoma

Abstract: Our data indicate that hypertension persists after removal of PCG/PGL in a substantial proportion of patients. Hypertensive heart disease is common, and cardiovascular events are frequent in patients with a history of PCC/PGL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
4
3
1
Order By: Relevance
“…However, the paraganglioma group received the same amount of antihypertensive medication post surgery as at diagnosis, despite normalization of blood pressure. Our improvement in blood pressure seems much better than others who have shown persistent hypertension in 51–79% at last follow-up [ 9 , 10 ]. Weismann et al [ 10 ] reported that only 38% had improved blood pressure using similar criteria as us, compared to 94% of our patients.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…However, the paraganglioma group received the same amount of antihypertensive medication post surgery as at diagnosis, despite normalization of blood pressure. Our improvement in blood pressure seems much better than others who have shown persistent hypertension in 51–79% at last follow-up [ 9 , 10 ]. Weismann et al [ 10 ] reported that only 38% had improved blood pressure using similar criteria as us, compared to 94% of our patients.…”
Section: Discussioncontrasting
confidence: 57%
“…Our improvement in blood pressure seems much better than others who have shown persistent hypertension in 51–79% at last follow-up [ 9 , 10 ]. Weismann et al [ 10 ] reported that only 38% had improved blood pressure using similar criteria as us, compared to 94% of our patients. On the other hand, our blood pressure follow-up was done 6–12 months post surgery, and we did not have long-term follow-up data of blood pressure.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…The diagnosis may be challenging as about 50% of patients are asymptomatic [ 10 ] or suffer from only unspecific signs or symptoms [ 9 , 11 ]. On the other hand, up to 20% may develop life-threatening hemodynamic instability leading to pulmonary edema, malignant arrhythmias, myocardial infarction, stroke, or sudden death [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%